Reliable robust tracking with application to aircraft control : LMI-based approaches - Liao, Fang. (2008)
This thesis presents four new approaches of the reliable robust tracking controller design for LTI systems. Several types of faults with respect to actuator faults and aircraft control/wing/tail surface impairment are modeled, and corresponding design approaches of reliable robust tracking controllers against such faults are presented.